PENGARUH FAKTOR KETEBALAN SKIN RESONATOR, DIAMETER LEHER RESONATOR, DAN VOLUME ISIAN RESONATOR (ACOUSTIC FILL) PADA KINERJA PENYERAPAN SUARA PANEL PEREDAM BERBASIS SERAT SABUT KELAPA - I Gusti Ayu Ratu Putri Maharani; R. Hari Setyanto; Susy Susmartini (Jurnal Ilmiah Teknik Industri, 2025)
Noise is an excessive repeated exposure to sound that can cause damage to humans or other living things. Continuous exposure to noise can cause health problems such as sleep disorders, hearing loss, stress disorders, and decreased work productivity. The way to control noise is by designing a sound absorber panel. The material used in the design of sound absorber panel is natural fiber. Coconut coir fiber has porosity and fiber structure that allows effective sound absorption. The physical shape of the sound absorber panel also affects the ability to absorb sound. In this research, three factors are used to see the sound absorption ability of the sound absorber panel, resonator skin thickness, diameter of resonator neck, and the acoustic fill. Variation of skin thickness are 6 mm and 9 mm, resonator neck diameter are 6 mm and 8 mm, and the acoustic fill are 8% and 9%. The result showed that the specimen with the variation of resonator skin thickness of 6 mm, resonator nec diameter of 6 mm, and acoustic fill of 9% was optimal in sound absorption with a decibel drop value of 3,939 dB.